Towards Green Rusunawa: Clean Water Utilization, Composting, and Urban Farming in Muara Baru Flats - Dion Notario; Ferdian Suprata; Meda Canti; Listya Utami Karmawan (MITRA: Jurnal Pemberdayaan Masyarakat, 2021)
Waste disposal and clean water management are some of the common social issues arising in densely populated settlements, including Muara Baru flats, Jakarta. Some programs have been carried out to overcome these two issues in Muara Baru, such as the construction of a Rain Water Harvesting (RWH) facility and the provision of Trash Banks. Nevertheless, adequate support for the residents is still needed to boost their awareness of proper clean water management and waste disposal and to encourage the formation of urban agriculture, which is expected to elevate their living standards. Therefore, a community empowerment program in Muara Baru was developed, consisting of three sections: education on clean water management, compost making training, and urban farming. The success of this program was then measured using questionnaires and focus group discussions. A majority of residents responded positively to the program and were willing to actively participate by preparing the land, making compost, planting seeds, or caring for the harvest. There were indeed some obstacles hampering the program's success, such as lack of commitment from the local community, climate change, water availability, and arable land availability. To overcome these barriers and to promote the program’s sustainability, some suggestions are to be proposed, including proper selections of plant types and provision of support and motivation for the local community.